2010
DOI: 10.1016/j.rbmo.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Growth of children conceived by IVF and ICSI up to 12years of age

Abstract: Recent studies have given conflicting results regarding growth in children born following assisted reproductive treatments up to the age of 18years. It has been suggested that children conceived via IVF may be taller than naturally conceived children and that this may due to subtle epigenetic alteration of imprinted genes as a result of the IVF process. A prospective match-controlled study was performed to investigate the growth of children born in the UK following standard IVF and intracytoplasmic sperm injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 27 publications
1
37
0
4
Order By: Relevance
“…The vast majority of these studies have not found any differences in the postnatal growth until 12 years old between ART and NC children (Sutcliffe et al, 2003;Bonduelle et al, 2004;2005;Belva et al, 2007;Knoester et al, 2008;Basatemur et al, 2010;Lee et al, 2010;Woldringh et al, 2011). However, some studies suggest that ART children are taller.…”
Section: Growth and Gonadal Developmentmentioning
confidence: 98%
“…The vast majority of these studies have not found any differences in the postnatal growth until 12 years old between ART and NC children (Sutcliffe et al, 2003;Bonduelle et al, 2004;2005;Belva et al, 2007;Knoester et al, 2008;Basatemur et al, 2010;Lee et al, 2010;Woldringh et al, 2011). However, some studies suggest that ART children are taller.…”
Section: Growth and Gonadal Developmentmentioning
confidence: 98%
“…This suggests that the complex IVF process as a whole, or an intrinsic aberration in the infertile population, is responsible for this increase, rather than the insemination method used. Indeed, follow-up of babies conceived via ICSI and standard insemination thus far has been relatively reassuring in that there appears to be no difference in cognitive or motor development, pubertal development, or major birth defects between standard insemination and ICSI-derived offspring (6,(26)(27)(28). Bonduelle et al found that sex chromosome aneuploidies were elevated in children conceived via ICSI, although the numbers of affected individuals were small (24,25).…”
Section: Q8mentioning
confidence: 99%
“…23 Overall, compared with spontaneous conceptions, both ICSI and IVF are associated with lower birth weight, preterm delivery and an increased prevalence of congenital malformations. 24,25 There have also been a variety of medical and psychosocial outcomes examined beyond the perinatal period demonstrating no specific differences between IVFand ICSI-conceived children in growth, 26 neurological, 27,28 cognitive 29 and socio-emotional development 30 and physical health. 31 From here on, this review will present studies that have specifically examined aspects of male infertility, noting that there is limited published material available on offspring outcomes in the presence of male infertility.…”
Section: Introductionmentioning
confidence: 99%